Transformation of accountants’ competencies as an element of accounting and analytical support - Lebedik, Petro (Herald of Economics, 2025)
Introduction. In modern conditions, the analysis of the transformation of the professional profile of an accountant in the context of accounting and analytical support of enterprises is of particular importance. Accounting personnel play a key role in the collection, processing and interpretation of data that serve as the basis for strategic and operational management. Therefore, it is important to understand which competencies are currently considered a priority by employers and how they are changing under the influence of digitalization. The purpose of the article is to substantiate the role of accounting personnel as a key element of the system of accounting and analytical support for the activities of enterprises. Research methods. The study used general scientific methods – analysis and synthesis (for structuring competencies), induction and deduction (for forming conclusions), comparison (to identify changes between 2024 and 2025), as well as generalization (to establish general trends). The main specific method was a content analysis of over 1500 job postings from international platforms (Indeed, Glassdoor, ZipRecruiter), which made it possible to identify the dynamics of requirements for the professional, personal, and digital competencies of accountants. To increase reliability, the data was cleaned of duplicatesand standardized. Results. The results obtained indicate the stability of requirements for basic professional skills of accountants, in particular accounting, management, and reporting. At the same time, an increase in the significance of analytical skills (+10 percentage points), problem-solving abilities (+15 percentage points), and digital competencies, including basic knowledge of AI tools (+4 percentage points), was noted. There is also a gradual convergence of the Ukrainian accountant profile with the international model. Prospects. Further research should focus on assessing the effectiveness of training accountants for digital challenges, studying the impact of AI on their functional responsibilities, comparing the transformation of competencies in Ukraine and the EU, as well as analyzing the prospects for new specializations within the profession – all of which will contribute to a scientifically sound modernization of the accountant’s role in the context of digital transformation.